STANDARDIZATION AND EVALUATION OF TWO MARKETED POLYHERBAL FORMULATION (GUTIKAS) - PALIWAL, SONIA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The study was designed as standardization and evaluation of two marketed polyherbal formulation (gutikas) for the treatment of skin disorder and antibacterial. Methods: Selected marketed polyherbal formulations were containing tulsi (Ocimum sanctum) and neem (Azadirachta indica) as a main ingredient. The standardization of the two polyherbal formulation was carried out as per official guidelines, in which the polyherbal tablet formulation was subjected that physiochemical characterization, phytochemical, and pharmaceutical parameter would serve as the identity of this polyherbal formulation. Results: Phytochemical test indicates the presence of alkaloid, glycosides, terpenoids, tannins, and steroids in both formulations. Parameters for loss of drying, pH, ash values, and extractive values documented. Pharmaceutical parameters, such as hardness, friability, weight variation, and disintegration, were found to be within acceptable values. Conclusion: From the result, it was concluded that polyherbal formulation of tulsi and neem tablet passes all the standardization and evaluation parameters and developed quality standard which can be used as a quality standard for polyherbal formulation.